Discussion Panel Human Factors in Everyday Life. (September 2013) - Sethumadhavan, Arathi; McLaughlin, Anne; Nichols, Tim; Pak, Richard; Smith, Mac
Majority of the sessions at the human factors and ergonomics society conferences in the recent years have focused on the applications of human factors and ergonomics in safety-critical domains, be it studying handoffs in health care, next gen and air traffic control or supervisory control of unmanned aerial vehicles. While this work is certainly important, there appears to be fewer sessions focused on how human factors can be integrated into everyday living. On any given day, users interact with a myriad of technology, tools, and equipment: smartphone alarm systems, microwaves, washing machines, navigation systems, sports gears, and video games. Unfortunately, a lot of these systems may not be designed with the same amount of attention to the cognitive, perceptual, and physical limitations and capabilities of humans as with safety-critical systems. While the main premise behind the use of technology is to lower human errors and improve efficiency, technology can contribute to inefficiencies and dissatisfaction if not designed well. The goal of this panel is to discuss how human factors and ergonomics can be applied to design technology and systems that are used in everyday activities, including sports, video gaming, and personal computing. The panelists will share their experiences with the audience, focusing on challenges and successes involved in designing such products. The panel will invite the audience to discuss ways to address the challenges and increase the successes.